A főrabbi vagy a plébános? : Kecskeméti Ármin és Juhász Kálmán magántanári habilitációs eljárásáról - Miklós, Péter (Közép-Európai Közlemények, 2015)
The author provides an overview of the archival materials of two habilitation procedures in the University of Szeged in the 1930’s years. Ármin Kecskeméti (1874–1944) was neolog chief rabbi in Makó, Kálmán Juhász (1892–1966) was roman catholic priest in Kübekháza. Kecskeméti’s successful habilitation process was in 1930–1931, Juhász’s failed process was in 1937–1938. According the opponent professors Kecskeméti’s scientific work testifies his hungarian national commitment, but the books and articles of Juhász representes his german scientific approach. Both their lives were ruined by totalitarian – nazi and communist – dictatorships. Ármin Kecskeméti has been a victim of the holocaust in 1944, Kálmán Juhász Kálmán removed the scientific life by the hungarian communist dictatorship after 1948.